The Royal Treatment: Temporality and Technology in The King’s Speech - Richman, Jared S. (Disability Studies Quarterly, 2020)
This essay examines the intersections of class, technology, and disability manifest within The King's Speech. It argues that the film obfuscates modern scientific and critical understanding of communication disorders by rendering stuttering as a moral failure rather than by attempting to understand it as a socially constructed condition contingent upon established societal and temporal norms. The essay identifies the social codes enforcing correct and eloquent speech that create a political and social climate for "compulsory fluency"—the socially imperative verbal facility promoted as necessary to participate in public life. Crucially and somewhat ironically, with its emphasis on the nobility of the title character, the film sublimates an inherent tension between media technology and the lingering social stigma surrounding disability. The King's Speech thus situates compulsory fluency as an essential component of modern kingship. By reading the film's strategic deployment of radio technology alongside its troubled representation of class and his fraught invocation of Shakespeare's Hamlet, the essay reads attitudes towards vocal disability within the context of royalty, patriarchy, and national identity. Ultimately, the essay locates The King's Speech as a film whose image of modern kingship grounds itself upon a notion of imperial authority as technologically constructed but ultimately disabled by a national fantasy of historical wholeness in the fabricated kinship between a monarch and his people.